If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 45 = -3x Reorder the terms: 45 + 6x = -3x Solving 45 + 6x = -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 45 + 6x + 3x = -3x + 3x Combine like terms: 6x + 3x = 9x 45 + 9x = -3x + 3x Combine like terms: -3x + 3x = 0 45 + 9x = 0 Add '-45' to each side of the equation. 45 + -45 + 9x = 0 + -45 Combine like terms: 45 + -45 = 0 0 + 9x = 0 + -45 9x = 0 + -45 Combine like terms: 0 + -45 = -45 9x = -45 Divide each side by '9'. x = -5 Simplifying x = -5
| -4y+7y=11y | | 0=9/4x-9 | | 5=9/4x-9 | | 2=9/4x-9 | | 1=9/4x-9 | | -16=k-12 | | 3x-12=-2x+2 | | 8-8c-8c-4b-4b= | | 5x-20=-3x+20 | | x-5-7=2(x+2) | | 12(x-3)-32=5(13+x) | | 92+53+115+2x+3x=540 | | 0=7/6x+6 | | 2(-8+6x)=-4 | | 2(5x+7)=-42+26 | | 5(-6x+3)=15 | | 1x-3=-4x+37 | | 1=7/6x+6 | | -1(5x-3)=1 | | 2x+42=-4x | | -5x+6-x=-6 | | 2x-8=-3x+22 | | 6x+7(2-x)=14-9x-8 | | Y=7/6(0)+6 | | 3x-9=-4x+19 | | 1x-4=-4x+36 | | 3(x+5)(x-10)=7 | | 79-17/8 | | 8=-3x+4x+1 | | 3(c-5)+4c(c-5)= | | 11x-7x=4 | | 3(x-4)=2(5x-11) |